1992
DOI: 10.1121/1.404211
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dynamic behavior of human middle ear using a finite-element method

Abstract: Applying the general-purpose finite-element package program (ISAP), a three-dimensional finite-element method (FEM) model of a human right middle ear, which included ossicles, was made and the mechanical properties and boundary conditions of the middle ear were determined by a comparison between the numerical results obtained from the FEM analysis and the measurement results of the fresh cadavers, normal subjects and patients, which were obtained by our developed sweep frequency middle ear analyzer (MEA). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 14 publications
3
74
0
Order By: Relevance
“…Funnell and Laszlo (1978) published the first study on the full-field motion of the cat eardrum model, and the eardrum was modeled by shell elements. Wada et al (1992) reported a preliminary study on FE modeling of the human TM vibration pattern (displacement amplitude) at two frequencies of 996 and 1,924 Hz. reported the TM motion as the displacement amplitude contour under middle ear static pressures (−2 and 2 kPa).…”
Section: Introductionmentioning
confidence: 99%
“…Funnell and Laszlo (1978) published the first study on the full-field motion of the cat eardrum model, and the eardrum was modeled by shell elements. Wada et al (1992) reported a preliminary study on FE modeling of the human TM vibration pattern (displacement amplitude) at two frequencies of 996 and 1,924 Hz. reported the TM motion as the displacement amplitude contour under middle ear static pressures (−2 and 2 kPa).…”
Section: Introductionmentioning
confidence: 99%
“…Material properties: The Young's modulus of the middle ear bones and ligaments were taken from Wada et al [9] and are shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 99%
“…Finite element modelling has been used to analyze middle ear mechanics, the most comprehensive model being that of Wada et al [8,9]. It includes the ear-canal, tympanic membrane, ossicles, the various muscles and ligaments of the middle ear as well as the middle ear cavities.…”
Section: Introductionmentioning
confidence: 99%
“…A number of groups have since used the finiteelement method to study the mechanics of the eardrum and ossicles in humans (Wada et al 1992;Beer et al 1999;Bornitz et al 1999;Prendergast et al 1999;Koike et al 2002;Sun et al 2002) and in cats (Funnell and Laszlo 1978;Funnell et al 1987;Ladak and Funnell 1996;Funnell et al 2005). The geometries have generally been oversimplified and material properties have often been based on curve fitting.…”
Section: Introductionmentioning
confidence: 99%